2015
DOI: 10.1371/journal.pone.0140250
|View full text |Cite
|
Sign up to set email alerts
|

Unique Microstructural Changes in the Brain Associated with Urological Chronic Pelvic Pain Syndrome (UCPPS) Revealed by Diffusion Tensor MRI, Super-Resolution Track Density Imaging, and Statistical Parameter Mapping: A MAPP Network Neuroimaging Study

Abstract: Studies have suggested chronic pain syndromes are associated with neural reorganization in specific regions associated with perception, processing, and integration of pain. Urological chronic pelvic pain syndrome (UCPPS) represents a collection of pain syndromes characterized by pelvic pain, namely Chronic Prostatitis/Chronic Pelvic Pain Syndrome (CP/CPPS) and Interstitial Cystitis/Painful Bladder Syndrome (IC/PBS), that are both poorly understood in their pathophysiology, and treated ineffectively. We hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 51 publications
4
81
0
1
Order By: Relevance
“…Other MAPP analyses examining cross-sectional clinical and neuroimaging data have also found more similarity than differences across men and women with UCPPS 5, 2930 . Also, neither income level (as a marker of social economic status) nor UCPPS chronicity were significant predictors of outcome.…”
Section: Discussionmentioning
confidence: 95%
“…Other MAPP analyses examining cross-sectional clinical and neuroimaging data have also found more similarity than differences across men and women with UCPPS 5, 2930 . Also, neither income level (as a marker of social economic status) nor UCPPS chronicity were significant predictors of outcome.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, several changes in brain structure and function have been identified in patients with UCPPS compared to healthy individuals [3; 10; 17; 19; 22; 27; 46], but it is unknown whether there are brain features that predict longitudinal symptom change in symptoms of UCPPS. Here, we begin the process of identifying such brain features by examining the ability of functional connectivity measures derived from resting state functional MRI (rs-fMRI).…”
Section: Introductionmentioning
confidence: 99%
“…A combination of alterations to the nervous system with endocrine, psychosocial, or immunological abnormalities leads to the chronic state of CP/CPPS. 4,[7][8][9][10] Colonoscopy is a common procedure for diagnosing a wide range of conditions and symptoms, including chronic abdominal or pelvic pain, neoplasms, and colitis. Numerous studies indicated that the colonoscopic examination itself may induce abdominal pain and transient bacterial infections.…”
Section: Introductionmentioning
confidence: 99%